МАКТАБГАЧА ЁШДАГИ БОЛАЛАРНИНГ ЖИСМОНИЙ КЎНИКМА ВА МАЛАКАЛАРИНИ РИВОЖЛАНТИРИШДА ҲАРАКАТЛИ ЎЙИНЛАРНИ ҚЎЛЛАШ - Нуриддинова, М. (SCIENCE and SOCIETY, 2020)
The article contains methodical recommendations how to organize moving games with pre-school children during the lessons in physical training.